Fertility status in wheat (Triticum aestivum) under long-term nutrient management practices in an Alfisol - CHAKRABORTY, RANABIR; SHARMA, V K; DAS, D; BISWAS, D R; MAHAPATRA, P; SHAHI, D K; BARMAN, MANDIRA; CHOBHE, KAPIL A; ANIL, AJIN S (The Indian Journal of Agricultural Sciences, 2021)
Soil samples were collected during 2018 from a long-term field experiment on soybean [Glycine max (L.) Merr.]- wheat (Triticum aestivum L.) system continuing since 1972 at Birsa Agriculture University, Jharkhand. The samples were analysed for available major and micro nutrient and biological properties at IARI, New Delhi. The treatments consisted of control, 100% N, 100% NP, 50% NPK, 100% NPK, 150% NPK, 100% NPK + FYM and 100% NPK + Lime. Highest grain yield of wheat was obtained with 100% NPK + FYM followed by 100% NPK + Lime. Whereas, in soybean, 100% NPK + Lime treatment recorded the highest yield, followed by 100% NPK + FYM. The highest available N (218 kg/ha) was found under 150% NPK, which was statistically similar to 100% NPK + FYM. Moreover, highest Bray-P (169 kg/ha) and available K (161 kg/ha) was observed in 100% NPK + FYM and 150% NPK treatment respectively. The DTPA extractable Fe, Mn, Zn and Cu were recorded in the range of 13.9-41.8 mg/kg, 31.1-60.6 mg/ kg, 0.64-1.94 mg/kg and 0.71-1.28 mg/kg, respectively under different nutrient management practices. Treatment 100% NPK + FYM recorded the maximum contents of available micronutrients. Acid phospho-monoesterase (AMP) activity and microbial pools such as microbial biomass carbon (MBC) and microbial biomass phosphorus (MBP) were also found to be highest in 100% NPK + FYM treatment.